New species of Typhlotanaidae (Crustacea, Tanaidacea) from the Brazilian coast: genera Hamatipeda, Meromonakantha and Paratyphlotanais, with description of Targaryenella gen. nov. - Segadilha, Juliana Lopes; Serejo, Cristiana Silveira; Błażewicz, Magdalena (Zootaxa, 2019)
Benthic samples collected along the Brazilian coast yielded the description of four new species from three genera of Typhlotanaidae: one Hamatipeda (H. prolata), one Meromonakantha (M. mauri) and two Paratyphlotanais (P. apletos and P. bessai). A new genus Targaryenella is erected to accommodate Meromonakantha anarsios and differences between Targaryenella and Meromonakantha are given. This study increases the total number of Tanaidacea species known for Brazil by 8% (50 to 54 species); the family Typhlotanaidae off the coast of Brazil is now represented by four known genera. Identification keys to the three genera are provided.